Phylogenetic And Genetic Analysis Of Tropical Bed Bug Cimex Hemipterus (F.) Population In Peninsular Malaysia - Masran, Siti Nor Ain Seri (2019)
The tropical bed bugs, Cimex hemipterus (Fabricus) wingless insects, is recognized scientifically as a significant public health problem. The association of bed bug populations between isolates in terms of geographical location with in-depth and significant understanding is important for developing effective control strategies. The study was conducted to understand the genetic reproduction pattern of the C. hemipterus population in terms of allelic variation, genetic diversity, population structure and phylogeography among tropical bed bug populations in Peninsular Malaysia. The phylogenetic study was carried out by using mitochondria cytochrome oxidase subunit I (COI) on twenty-two tropical bug populations with three pooled bed bugs respectively. The analysis of COI gene data produced a phylogenetic tree with a major monophyletic clade consisting of two groups of Ch01 and Ch02. The Ch02 group was consist of Bandar Hilir populations, in contrast to other populations that make up a single cluster. The Ch01 group shows similarities with some of the COI genes of the C. hemipterus from Thailand, suggesting the similarity of population variation. However, the variation of the observed COI gene is low. Next, from NGS analysis, 50 microsatellite markers were developed, with seven microsatellite markers selected for the polymorphisms study. A total of 220-bed bugs samples were genotyped with seven species-specific polymorphic microsatellite markers and showed 6-14 allele per locus, with high genetic diversity observed among populations. The mean observed and expected heterozygosity of the overall population were 0.280 and 0.828.